Homothetic functions with allen's perspective and its geometric applications - Aydin, M.E.; Ergut, M. (University of Kragujevac, Faculty of Science, 2014)
In this paper, we completely classify the homothetic functions of 2 variables by using their Allen's matrices. We give some applications of Allen's matrices to composite functions. Several geometric results are also obtained for graphs of homothetic functions.
Keywords: Allen's elasticity of substitution; Generalized acms production function; Generalized cobb-douglas production function; Homothetic production function